The Urgency of the Teaching Method of the Prophet Muhammad and Its Implications for Millennial Era Learning Models - Arfani, Arlinda Ayu Diah; Iskarim, Mochammad (Tadibia Islamika: Journal of Holistic Islamic Education, 2023)
The Prophet Muhammad's attention to education extended to the development of a system, theoretical strategies, and teaching methods. Remarkably, many of the teaching methods he employed during his time remain relevant today. His insights into teaching methods have proven to be capable of addressing various educational challenges faced by humanity. Nevertheless, it is sometimes assumed that contemporary learning models are solely derived from Western influences, overlooking the significant contributions of the Prophet Muhammad in this regard. While methods refer to the means of acquiring knowledge, learning models are the outcomes of these teaching methods. Over time, the teaching methods imparted by the Prophet Muhammad have had a profound impact on contemporary learning models. The aim of this research is to analyze the urgency of the Prophet Muhammad's Islamic teaching methods and their contributions to contemporary millennial-era learning models. A qualitative approach, supported by library research, was employed as the research method. Data validity was ensured by reviewing relevant sources, including accredited journals, scholarly articles, and related books. This research demonstrates that the teaching methods of the Prophet Muhammad are of great significance and have substantial implications for millennial-era learning models. This is substantiated by the contemporary learning models that incorporate various teaching methods taught by the Prophet Muhammad, which have proven effective in addressing learning challenges in the millennial era. Consequently, it is crucial to consider appropriate and relevant teaching methods, similar to those imparted by the Prophet Muhammad, when developing a learning model.